HUBUNGAN POLA ASUH ORANG TUA DENGAN KEJADIAN TEMPER TANTRUM PADA ANAK USIA PRASEKOLAH DI KELOMPOK BERMAIN PERMATA - ALINI ALINI; WIRDATUL JANNAH (Universitas Pahlawan Tuanku Tambusai, 2019)
In Indonesia, within one year there are 23-83% of preschool-aged children have experienced tempertantrum. The causes of temper tantrums vary, one of which is parenting. As a result of this temper tantrum is quite dangerous, including the child will experience physical injury during emotional outbursts, and temper tantrum children as adults will have low self-control and irritability. The purpose of this study was to determine the relationship between parenting parents with the occurrence of temper tantrums in preschool children. This type of research is quantitative with cross sectional design. The sample in this study were all students enrolled in the Permata Bunda Play Group in Pulau Sarak village, amounting to 30 people. The sampling technique in this research is to use a total sampling technique. Analysis of the data used is univariate and bivariate analysis. The results showed there is a relationship between democratic parenting with the occurrence of temper tantrums (p value = 0.033 Î± Î± 0.05), there is a relationship between authoritarian parenting with temper tantrum events (p value = 0.041 â‰¤ Î± 0.05), there is no relationship between permissive parenting with the occurrence of temper tantrums (p value = 0.0274 â‰¥ Î± 0.05). Parents are expected to be able to apply good parenting, such as democratic parenting where the parenting is considered good applied to children because the risk of temper tantrums in children is smaller compared to authoritarian and permissive parenting.